Effectiveness of fermentation broth of Cordyceps sinensis for primary insomnia: a randomized clinical trial with digital health tool - Zhao, Shuting; Wang, Ziqian; Fan, Xiaxia; Shu, Xuanhao; Chen, Qiao; Zhou, Yibo; Fu, Yongzhi; Yu, Zheng; Grzegorzek, Marcin; Huang, Xinyu; Zheng, Chengwen; Gan, Yanxiong; et al. (Frontiers in Neurology, 2025)
BackgroundCordyceps sinensis is widely used in Traditional Chinese Medicine and dietary supplements to tonify the kidney, lung, and heart, as well as to calm the mind. The fermentation broth of Cordyceps sinensis (FBCS), containing cordycepin, has shown potential in various healthcare applications.MethodsNinety patients with primary insomnia were divided into two groups: the FBCS group (n = 45) and the control group (n = 45). The FBCS group received Cordyceps fermentation liquid drink (150 ml/day), while the control group received a placebo (150 ml/day). Both groups were supported by Digital Health Tools (DHT) for medication supervision. Pittsburgh Sleep Quality Index (PSQI) scores were assessed and collected through the DHT application at the initial baseline period, 14, and 28 days after treatment.ResultsSignificant main effects of time and time × group interaction on the PSQI total score and all subcomponents. Significant group effects were also observed for most subcomponents, except for Sleep Disturbances and Daytime Function, indicating greater improvements in the FBCS group over time. After 14 and 28 days of FBCS consumption, the treatment group demonstrated greater reductions in PSQI total scores compared to the control group. Subcomponent analysis revealed greater improvements in the FBCS group compared to the control group at both time points. Specifically, Sleep Quality scores decreased by −0.89 vs. −0.50 at Day 14 and −1.32 vs. −0.45 at Day 28. Sleep Onset Latency improved by −0.75 vs. −0.20 at Day 14 and −1.32 vs. −0.27 at Day 28. Sleep Duration scores decreased by −0.86 vs. −0.20 at Day 14 and −1.20 vs. −0.23 at Day 28. Sleep Efficiency showed a decline of −0.82 vs. +0.23 at Day 14 and −1.11 vs. +0.30 at Day 28. For Sleep Disturbances, the FBCS group improved by −0.41 vs. −0.05 at Day 14 and −0.55 vs. +0.14 at Day 28. Lastly, Daytime Function scores decreased by −0.73 vs. −0.07 at Day 14 and −0.95 vs. −0.18 at Day 28.ConclusionThe FBCS demonstrated significant effectiveness in improving overall sleep outcomes among patients with primary insomnia. Moreover, the use of DHT enhanced patient adherence and facilitated reliable data collection.Clinical trial registrationhttps://www.chictr.org.cn/searchprojEN.html, identifier ChiCTR2100051187.